Association of Anemia with Outcomes of Acute Heart Failure. Issue 2 (February 2018) - Halawa, Ahmad; Burton, M. Caroline; Maniaci, Michael J.; Shapiro, Brian P.; Yip, Daniel S.; Hodge, David O.; Vargas, Emily R.; Dawson, Nancy
Abstract : Objectives: Anemia is common in patients presenting with acute congestive heart failure (CHF); when hemoglobin (HGB) declines to low levels, it can result in worse outcomes. The aim of this study was to determine a level of HGB on admission or discharge that affects outcomes in patients with CHF and then to evaluate the effect of the low HGB levels on these outcomes. Methods: We conducted a retrospective cohort study of 756 patients admitted with acute CHF during the period January 1, 2011–December 31, 2014. We used multivariable regression analysis to evaluate the relation among HGB levels and three major outcomes: 3-year mortality, 30-day readmission rate, and length of stay (LOS). Results: Compared with patients with HGB ≥10 g/dL, patients with HGB <10 g/dL on discharge from the hospital had higher mortality (3-year survival 46% vs 33%, P = 0.023) and 30-day readmission rates (23% vs 14%; P = 0.008) and increased LOS (4.8 vs 3.2 days, P < 0.001). Patients with admission HGB <10 g/dL had higher mortality rates (3-year survival 45% vs 32%, P = 0.019) and increased LOS (4.5 vs 3.4 days, P = 0.014). A lower admission HGB value was associated with higher 30-day readmission rates, but it was not statistically significant ( P = 0.06). Conclusions: An HGB level <10 g/dL on admission or discharge in patients hospitalized with acute CHF is associated with a significantly worse outcome. Abstract : Anemia is common in patients presenting with acute congestive heart failure. The aim of this study was to determine whether the negative impact worsened at certain levels of anemia; results showed that a hemoglobin level <10 was associated with worse outcomes.